[World Food Day Exhibition] - (:unkn) unknown (The Public Relations Department. Caroni (1975) Limited, Trinidad and Tobago, 2013)
Dr. Will Georges, Agronomist (left), speaks to an attendee during a World Food Day exhibition at the Caroni Research Station.
Cataloger's title
Keywords: Agriculturalists -- Trinidad and Tobago; Caroni (1975) Limited